Surveillance of Culicoides biting midges in northern Honshu, Japan, during the period of Akabane virus spread - YANASE, Tohru; HAYAMA, Yoko; SHIRAFUJI, Hiroaki; TSUTSUI, Toshiyuki; TERADA, Yutaka (Journal of Veterinary Medical Science, 2019)
A surveillance of Culicoides biting midges with light suction traps was conducted in the northern region of Honshu, main island of Japan, during the summers and autumns of 2009 and 2010. A total of 106 trap collections across 37 cattle farms were investigated for the structure and distribution of Culicoides species. Forty-thousand and one hundred forty-nine specimens of Culicoides biting midges were identified at the species level, and ≥19 species were included in the specimens. Culicoides oxystoma, which is a known major vector of Akabane virus (AKAV), appeared not to have expanded in northern Honshu during the surveillance. Of the potential AKAV vectors suggested by a previous laboratory experiment, C. tainanus and C. punctatus widely infested cowsheds across northern Honshu. The AKAV circulation was confirmed by serological surveillance of sentinel cattle in northern Honshu during the summer and autumn of 2010 and, consequently, >200 calves affected by the virus were identified as of spring 2011. Our surveillance demonstrated that C. tainanus and C. punctatus were widely spread and often dominated at cattle farms in/around the seroconverted regions, and our results thus suggest that these species played a critical role in the AKAV transmission in 2010. Because the distribution ranges of C. tainanus and C. punctatus cover almost all of mainland Japan, a potential risk of AKAV transmission might be expected even in areas outside the range of C. oxystoma.